2020
DOI: 10.1002/ece3.6547
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of herbivores between leaves matches their performance only in the absence of competitors

Abstract: Few studies have tested how plant quality and the presence of competitors interact in determining how herbivores choose between different leaves within a plant. We investigated this in two herbivorous spider mites sharing tomato plants: Tetranychus urticae , which generally induces plant defenses, and Tetranychus evansi , which suppresses them, creating asymmetrical effects on coinfesting competitors. On uninfested plants, both herbivore species preferred young lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 81 publications
2
26
0
Order By: Relevance
“…The likelihood of such evolutionary rescue increases with the amount of standing genetic variation available for adaptation to the sink environment [ 15 , 66 , 67 ]. The WCM population we used to test adaptation to brome was established from a large number of individuals collected at several distant geographical locations, a procedure that is likely to maximize genetic variance [ 53 ]. By following this method, we ensured a much larger level of genetic variation than that usually found in populations used in most studies of experimental evolution, which have shown adaptation to a given environment [ 19 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of such evolutionary rescue increases with the amount of standing genetic variation available for adaptation to the sink environment [ 15 , 66 , 67 ]. The WCM population we used to test adaptation to brome was established from a large number of individuals collected at several distant geographical locations, a procedure that is likely to maximize genetic variance [ 53 ]. By following this method, we ensured a much larger level of genetic variation than that usually found in populations used in most studies of experimental evolution, which have shown adaptation to a given environment [ 19 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is ample evidence that herbivorous mites use different types of cues upon which they base their decision to undertake aerial dispersal [ 50 , 51 ]. Moreover, they are also ambulatory dispersers, using cues to move from or towards patches [ 52 , 53 ]. Here, we evaluate these two types of dispersal in WCM exposed to wheat or brome.…”
Section: Methodsmentioning
confidence: 99%
“…Another possible reason why the findings did not support our hypothesis is the effects of resource competition among herbivores. In some cases, resource competition among herbivores influences herbivore distribution (e.g., Suzuki 1986;Schoonhoven et al, 2005;Godinho et al, 2020). A previous study pointed out that G. grisescens is vulnerable to resource competition from G. atrocyanea (Suzuki, 1986).…”
Section: Preferences and Distribution Of Leaf Beetlesmentioning
confidence: 99%
“…All experiments were performed with outbred populations of T. urticae and T. evansi spider mites, formed via controlled crosses among four T. evansi and three T. urticae populations collected in different locations in Portugal (Godinho et al 2020b). Before the experiment, spider mite populations were maintained in boxes containing leaves detached from five-week-old tomato plants (Solanum lycopersicum, var MoneyMaker), with their petiole in a small pot containing water, under controlled conditions (25 ºC, 68% of humidity, photoperiod of 16 hours light/8 hours dark).…”
Section: Model System Species Characteristics and Maintenance Of Experimental Populationsmentioning
confidence: 99%